Integrative approaches to nutrient management in tomato cultivation for improved sustainability and productivity - Li, Yubo; Zhang, Ruifang; Zhang, Chi; Li, Qingyun; Nie, Lanchun; Wang, Can; Wang, Xin-Xin (Frontiers in Plant Science, 2025)
Tomato is a vital crop within agricultural production systems and ranks among the most in-demand vegetables on the market, but tomato production faces significant challenges due to long-term cultivation practices, including soil successive cropping obstacles, nutrient imbalances, reduced microbial diversity, and the accumulation of allelopathic substances. Previous studies show that tomatoes exhibit substantial differences in yield and quality between integrated and conventional systems, primarily attributed to its high nutrient demands. This review synthesizes the most relevant scientific literature worldwide to examine the current state of knowledge regarding crop nutrition and soil fertility management in tomato production systems. It systematically analyzes the impacts of nutrient solutions, green manures, soil amendments, and biostimulants on both tomato yield and quality. The main findings indicate that conventional management methods lead to constrained tomato yields due to degraded soil fertility and inadequate nutrient supply. Therefore, integrated soil-tomato system strategies are required to enhance productivity and meet consumer demands. Additionally, this review uniquely integrates multidisciplinary approaches to highlight synergistic strategies for optimizing both yield and quality. We identify a critical gap in long-term comparative studies on soil-tomato system management and emphasize the need for consumer-oriented quality metrics in future research. By synthesizing global evidences, this work provides a comprehensive framework for sustainable tomato production beyond conventional nutrient-focused practices.